Enhancing Students' Reading comprehension through Venn Diagram strategy And Know, Want, Learn (KWL) Strategy. - Katemba, Caroline Victorine; Sihombing, Natalia Maria (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
The purpose of this study is to find out the improvement of students’ reading comprehension between those who acquire Venn diagram strategy and those who acquire Know, Want, Learn (KWL) chart strategy. This study used quantitative research method and comparative design by measuring the achievement of pre-test and post-test. The participants of the study were 64 students’ of Grade X of SMA N 1 Lembang, Bandung Barat in grade X MIPA 6 and X MIPA 7. They were divided into 2 groups. The students of grade X MIPA 6 acquired K.W.L chart while the students of grade X MIPA 7 acquired Venn diagram. The instrument used in this research is descriptive test. The result of this study shows that there is no significant difference on students reading comprehension improvement between those who acquired Venn diagram and those who acquired K.W.L and for the gender’s group there is no significant difference in reading comprehension improvement.